Pathophysiology of Angiotensin II-Mediated Hypertension, Cardiac Hypertrophy, and Failure: A Perspective from Macrophages - Kelly Carter; Eshan Shah; Jessica Waite; Dhruv Rana; Zhi-Qing Zhao (Cells)
Heart failure is a complex syndrome characterized by cardiac hypertrophy, fibrosis, and diastolic/systolic dysfunction. These changes share many pathological features with significant inflammatory responses in the myocardium. Among the various regulatory systems that impact on these heterogeneous pathological processes, angiotensin II (Ang II)-activated macrophages play a pivotal role in the induction of subcellular defects and cardiac adverse remodeling during the progression of heart failure. Ang II stimulates macrophages via its AT1 receptor to release oxygen-free radicals, cytokines, chemokines, and other inflammatory mediators in the myocardium, and upregulates the expression of integrin adhesion molecules on both monocytes and endothelial cells, leading to monocyte-endothelial cell-cell interactions. The transendothelial migration of monocyte-derived macrophages exerts significant biological effects on the proliferation of fibroblasts, deposition of extracellular matrix proteins, induction of perivascular/interstitial fibrosis, and development of hypertension, cardiac hypertrophy and heart failure. Inhibition of macrophage activation using Ang II AT1 receptor antagonist or depletion of macrophages from the peripheral circulation has shown significant inhibitory effects on Ang II-induced vascular and myocardial injury. The purpose of this review is to discuss the current understanding in Ang II-induced maladaptive cardiac remodeling and dysfunction, particularly focusing on molecular signaling pathways involved in macrophages-mediated hypertension, cardiac hypertrophy, fibrosis, and failure. In addition, the challenges remained in translating these findings to the treatment of heart failure patients are also addressed.